2020
DOI: 10.1055/s-0040-1716870
|View full text |Cite
|
Sign up to set email alerts
|

Histological Assessment of Wallerian Degeneration of the Rat Tibial Nerve Following Crush and Transection Injuries

Abstract: Background Wallerian degeneration (WD) following peripheral nerve injury (PNI) is an area of growing focus for pharmacological developments. Clinically, WD presents challenges in achieving full functional recovery following PNI, as prolonged denervation of distal tissues for an extended period of time can irreversibly destabilize sensory and motor targets with secondary tissue atrophy. Our objective is to improve upon histological assessments of WD. Methods Conventional methods utilize a qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
2
2
0
4
Order By: Relevance
“…Among the histological preparations assessed in the present study, we were surprised to see the consistent extent of axon sparing, especially among the small myelinated fibers. Compared to our previous study, the sequential breakdown of the axoplasm prior to myelin sheath was very similar to the Wallerian degeneration observed 5 days post-crush in the rat tibial nerve (Kerns et al, 2020 ). In the present study, the sequence of the observed changes was a result of injury itself, rather than Wallerian degeneration.…”
Section: Discussionsupporting
confidence: 87%
“…Among the histological preparations assessed in the present study, we were surprised to see the consistent extent of axon sparing, especially among the small myelinated fibers. Compared to our previous study, the sequential breakdown of the axoplasm prior to myelin sheath was very similar to the Wallerian degeneration observed 5 days post-crush in the rat tibial nerve (Kerns et al, 2020 ). In the present study, the sequence of the observed changes was a result of injury itself, rather than Wallerian degeneration.…”
Section: Discussionsupporting
confidence: 87%
“…Nerve transection results in histological changes of intrafascicular and extrafascicular structures (Turgut et al, 2005;Cosovic et al, 2017;Kerns et al, 2021). To study the neuroprotective effect of melatonin as a proregenerative substance we have observed the intrafascicular structures of the rat sciatic nerve with the emphasis on degenerating and regenerating nerve fibers, changes of the myelin sheath, connective tissue of the endoneurial compartment and the endoneurial tubes.…”
Section: Discussionmentioning
confidence: 99%
“…3) with leupeptin after transection and repair, but not crush may have stemmed from the similarity of a crush injury of this magnitude to a segmental defect, which is more damaging than a transection due to the axon-less gap between proximal and distal segments that the recovering nerve needs to bridge. Recent studies have shed light on potential differences between outcomes and responses in peripheral nerve to transection and repair versus crush injuries [17,18], namely, there is an observable difference in inflammation, target muscle atrophy, and growth cone generation between the two injury types. Leupeptin, a calpain inhibitor, can halt Wallerian degeneration that is responsible for these processes described previously.…”
Section: Discussionmentioning
confidence: 99%